2014
DOI: 10.1111/echo.12510
|View full text |Cite
|
Sign up to set email alerts
|

Right Atrial Appendage Aneurysm: A Systematic Review

Abstract: Right atrial appendage aneurysm although rare may be associated with significant morbidity. Surgical resection is indicated in symptomatic patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
70
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(75 citation statements)
references
References 14 publications
4
70
0
Order By: Relevance
“…A recent review identified just 17 cases reported in the literature to date, with only 3 cases identified in neonates. 1 These aneurysms can be associated with tachyarrhythmia, intracardiac thrombus formation, thromboembolism, and right ventricular compression precipitating heart failure. 1,2 In some instances, enlargement of the appendage may be related to idiopathic dilation of the entire right atrium, an entity that has been associated with sudden death.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A recent review identified just 17 cases reported in the literature to date, with only 3 cases identified in neonates. 1 These aneurysms can be associated with tachyarrhythmia, intracardiac thrombus formation, thromboembolism, and right ventricular compression precipitating heart failure. 1,2 In some instances, enlargement of the appendage may be related to idiopathic dilation of the entire right atrium, an entity that has been associated with sudden death.…”
mentioning
confidence: 99%
“…1 These aneurysms can be associated with tachyarrhythmia, intracardiac thrombus formation, thromboembolism, and right ventricular compression precipitating heart failure. 1,2 In some instances, enlargement of the appendage may be related to idiopathic dilation of the entire right atrium, an entity that has been associated with sudden death. 3 We present the case of a neonate diagnosed in utero with a right atrial appendage aneurysm that dramatically enlarged during the first weeks of life.…”
mentioning
confidence: 99%
“…Correct diagnosis is necessary for planning therapy. 10 The diagnosis of right atrial aneurysm can be established with echocardiography, angiography, CT, or MRI. In our case, right atrial aneurysm was diagnosed by echocardiography, TEE, and confirmed by CT angiography.…”
Section: A Rare Case Of Asymptomatic Giant Rightmentioning
confidence: 99%
“…He had no cardiac symptoms and physical exami- arrhythmic complications. 6 The common arrhythmias are supraventricular arrhythmias such as AF. 7 While symptomatic patients and those with an enlarging aneurysm should undergo surgical resection, a conservative approach has been recommended for asymptomatic patients.…”
mentioning
confidence: 99%
“…7 While symptomatic patients and those with an enlarging aneurysm should undergo surgical resection, a conservative approach has been recommended for asymptomatic patients. 6 Asymptomatic patients managed conservatively should receive anticoagulation for the prevention of thrombus formation. Because the present patient was asymptomatic but had a large aneurysm with a whirling blood flow and LGE of the atrial myocardium, treatment consisted of anticoagulation and conservative management with annual imaging surveillance.…”
mentioning
confidence: 99%